Exploring the Performance, Simulation, Design, and Construction of a Closed Solar Swimming Pool in Kirkuk City - Abed, Fayadh; Ali, Hussein Hayder Mohammed; Bayraktar , Nursan (Advances in Mechanical and Materials Engineering, 2023)
Indoor swimming pools are sports or entertainment facilities that require substantial energy to heat the pool water and maintain a comfortable atmosphere in compliance with international standards. However, traditional methods of heating swimming pools using fuels or electricity often result in high operational costs and environmental pollution. To address these challenges, solar water heating has emerged as the most significant and environmentally friendly technology. Consequently, the construction of solar-powered swimming pools has become a prominent issue, drawing considerable attention from governments worldwide. Solar energy is currently being utilized in various applications, with water heating in residential settings being one of the most popular ones. Iraq, known for its high solar energy potential, stands to benefit greatly from adopting and designing solar swimming pools. The proposed design incorporates essential components such as the swimming pool, pump, filter, control valves, and the solar collector. This study explores the influence of flow rate on the solar collector’s performance and its relationship with pool size under varying weather conditions in Kirkuk city. The month of February, characterized by lower solar radiation intensity and air temperature, was selected for the investigation. This study provides insights into heating indoor swimming pools using solar energy, examining the types of solar collectors, filters, and pumps involved. By offering guidance in the system design process, our research can be instrumental in facilitating the installation of such systems.